Thermally-driven coalescence in thin liquid film flowing down a fibre. (6th April 2021) - Ji, Hangjie; Falcon, Claudia; Sedighi, Erfan; Sadeghpour, Abolfazl; Ju, Y. Sungtaek; Bertozzi, Andrea L.
Abstract: Abstract : This paper presents a study on the dynamics of a thin liquid film flowing down a vertical cylindrical fibre under a streamwise thermal gradient. Previous works on isothermal flows have shown that the inlet flow and fibre geometry are the main factors that determine a transition from the absolute to the convective instability flow regimes. Our experiments demonstrate that an irregular wavy pattern and bead coalescence, which are commonly seen in the convective regime, can also be triggered by applying a thermal gradient along the fibre. We develop a lubrication model that accounts for gravity, temperature-dependent viscosity and surface tension to describe the thermal effects on downstream bead dynamics. Numerical simulations of the model show good agreement between the predicted droplet coalescence dynamics and the experimental data.